HYPERTENSION AND CHRONIC KIDNEY DISEASE : A SYSTEMATIC REVIEW - Effendy, Kgs. Mahendra (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
The frequency of chronic kidney disease, often known as CKD, is on the rise and affects 10–15% of the population around the world. Approximately one percent of adult Americans are affected by chronic kidney disease (CKD). The presence of reduced kidney function (an estimated glomerular filtration rate [eGFR] of less than 60 mL/min/1.73 m2) or kidney damage (usually demonstrated by the presence of proteinuria) that has lasted for more than three months is what is considered to be chronic kidney disease (CKD). At the moment, hypertension, a problem that has an effect on public health on a global scale, is the leading contributor to the overall illness burden. It is the single most significant modifiable risk factor that contributes to cardiovascular disease, stroke, and renal failure. Uncontrolled hypertension is linked to a higher risk of developing chronic kidney disease (CKD), which is also regarded to be a consequence of hypertension that is not under control. One of the most common factors leading to CKD is hypertension. The connection between high blood pressure and chronic renal disease is a convoluted one that elevates the probability of negative outcomes in the cardiovascular and cerebrovascular systems. According to the findings of this study, the percentage of hypertension patients who also have CKD is significantly higher than that of patients in the other groups. Additionally, the mean systolic and diastolic blood pressure of patients with CKD was found to be higher than that of those who did not have CKD.